1998
DOI: 10.1016/s0378-1097(98)00352-8
|View full text |Cite
|
Sign up to set email alerts
|

Quorum-sensing and siderophore biosynthesis in Pseudomonas aeruginosa: lasRllasI mutants exhibit reduced pyoverdine biosynthesis

Abstract: Cell density-dependent gene expression in Pseudomonas aeruginosa is controlled, in part, by the quorum-sensing regulator LasR. IasR null mutants exhibited a reproducible 2-fold decrease in production of the catecholate-hydroxamate siderophore pyoverdine during grown under iron-limiting conditions. Similarly, lasl mutants defective in the biosynthesis of the autoinducer PAI-also exhibited a 2-fold decrease in pyoverdine production which could be largely restored upon addition of exogenous PAI-I. IasR mutants we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
94
1
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(99 citation statements)
references
References 6 publications
3
94
1
1
Order By: Relevance
“…PvdS regulates expression of genes required for pyoverdine production, and is therefore upregulated when P. aeruginosa is in an iron-deficient environment. Pyoverdine upregulates production of itself as well as protease IV (Lamont et al, 2002) and its synthesis is also controlled by lasRI (Stintzi et al, 1998). In the current study, the lowprotease-producing isolates also demonstrated low pyoverdine production.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PvdS regulates expression of genes required for pyoverdine production, and is therefore upregulated when P. aeruginosa is in an iron-deficient environment. Pyoverdine upregulates production of itself as well as protease IV (Lamont et al, 2002) and its synthesis is also controlled by lasRI (Stintzi et al, 1998). In the current study, the lowprotease-producing isolates also demonstrated low pyoverdine production.…”
Section: Discussionmentioning
confidence: 99%
“…Controlled expression of several key P. aeruginosa virulence factors, including elastase (lasB) (Pearson et al, 1997), exotoxin A , type II secretory pathway proteins (xcp) (Chapon-Hervé et al, 1997) and pyoverdine (Kim et al, 2005;Stintzi et al, 1998) are mediated by population density bio-sensor mechanisms, a process known as quorum sensing. P. aeruginosa has two quorum-sensing systems, the Las and Rhl systems, each influencing the expression of a range of virulence factors (Passador et al, 1993;Pearson et al, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Hence, some of the observed alterations in the transcriptome profile of the rsmA mutant may be due to the direct effect of the rsmA mutation on the QS network, since RsmA negatively regulates lasI and rhlI . For example, the increase in 3-oxo-C12-HSL in the rsmA mutant ) may contribute to the increase in expression of the pyoverdine biosynthetic genes (Stintzi et al, 1998;Whiteley et al, 1999) and sodM (Hassett et al, 1999), both regulated by the QS system. However, although inactivation of rsmA affects AHL synthesis, this does not appear to have a dramatic effect on expression of all QSregulated genes.…”
Section: Discussionmentioning
confidence: 99%
“…Many bacteria secrete iron-chelating molecules to acquire iron for their own growth. Siderophores are low-molecular-weight iron-chelating compounds, and their production is reportedly controlled by quorum sensing (13,32). To examine whether siderophore synthesis in P. syringae pv.…”
Section: Detection Of Ahls and Northern Analysismentioning
confidence: 99%
“…Iron uptake using siderophores has been reported to be regulated by the quorum-sensing system in P. aeruginosa (32). Because environmental iron is almost insoluble at biological pH, many bacteria have developed systems to acquire iron by using siderophores, which show high affinity for iron(III) (28).…”
Section: Vol 188 2006mentioning
confidence: 99%